Design and Development of A Website-Based Inventory Management System: A Case Study of Al-Mardliyah Bahrul Ulum Islamic Boarding School Canteen - Munawarah Munawarah; Igo Ardiasnyah Harlis (SAINTEKBU, 2025)
The development of information technology in the digital era is very rapid and influences various aspects of life, including stock management. The Al-Mardliyah Bahrul Ulum Islamic Boarding School canteen, as a business unit that provides food and drinks for students, currently still uses a manual stock recording system that is prone to errors and inefficiencies. This research aims to design and build a web-based stock application to increase efficiency and accuracy in managing stock in the canteen. Using the waterfall software development model, this application is designed to have features such as automatic stock recording, low stock notifications, and automatic reporting. System test results show that this application can reduce stock processing errors, make reporting easier, and increase security and ease of data access. By implementing this web-based stock application, it is hoped that canteen operations will become more efficient and effective, better supporting the needs of students.